COVID‐19 and venous thromboembolism: A narrative review. Issue 2 (15th February 2022) - Angelini, Dana E.; Kaatz, Scott; Rosovsky, Rachel P.; Zon, Rebecca L.; Pillai, Shreejith; Robertson, William E.; Elavalakanar, Pavania; Patell, Rushad; Khorana, Alok
Abstract: COVID‐19 (severe acute respiratory syndrome coronavirus 2 [SARS‐CoV‐2]) is associated with coagulopathy through numerous mechanisms. The reported incidence of venous thromboembolism (VTE) in hospitalized patients with COVID‐19 has varied widely, and several meta‐analyses have been performed to assess the overall prevalence of VTE. The novelty of this coronavirus strain along with its unique mechanisms for microvascular and macrovascular thrombosis has led to uncertainty as to how to diagnose, prevent, and treat thrombosis in patients affected by this virus. This review discusses the epidemiology and pathophysiology of thrombosis in the setting of SARS‐CoV‐2 infection along with an updated review on the preventative and treatment strategies for VTE associated with SARS‐CoV‐2 infection.